The role of whey on the performance and campylobacteriosis in broiler chicks. (27th August 2018) - Tsiouris, V; Economou, E; Lazou, T; Georgopoulou, I; Sossidou, E
ABSTRACT: The objective of the present study was to investigate the effect of the whey on broiler chicks' performance, welfare, and caecal Campylobacter counts under experimental and field conditions. In the experimental study, 120-d-old broiler chicks were randomly allocated to four treatment groups, as described below: group A, which served as negative control; group B, fed with a diet supplemented with 1% whey; group C, challenged with Campylobacter jejuni ; and group D, supplemented with 1% whey and challenged with C. jejuni, respectively. Performance indexes and caecal C. jejuni counts were calculated. In addition to the performance indexes, the hock burn and the foot pad dermatitis lesions score were measured to assess the welfare status of broiler chicks. In order to evaluate the use of whey under field conditions, a second study was performed in a broiler farm with two identical houses. The evaluation of the experimental data revealed that the use of whey did not affect significantly the performance ( P ≤ 0.05) and the caecal C. jejuni counts ( P ≤ 0.05). There were neither footpad dermatitis lesions nor hock burn lesions in any of the experimental groups. In the field study, the use of whey had no effect on the performance indexes ( P ≤ 0.05). It can be concluded that the addition of whey has no negative effect on poultry and may provide an alternative natural feed additive for the broiler feed industry.